The Effect of Entrepreneurial Competence, Market Orientation, Product Quality, and Product Innovation on Competitive Advantage - Dewi Sri Murwati; Anisah, Hastin Umi (Open Access Indonesia Journal of Social Sciences, 2024)
MSMEs are the backbone of the Indonesian economy, contributing significantly to GDP and employment. However, they face the challenge of increasingly fierce competition, especially with market revitalization plans that can increase business competition. This research aims to analyze the influence of entrepreneurial competence, market orientation, product quality and product innovation on the competitive advantage of MSMEs in the clothing trade sector at Sudimampir Market, Banjarmasin. This research uses a quantitative approach with 95 respondents who are owners/managers of MSMEs in the clothing trade sector at Sudimampir Market. The sampling technique used purposive sampling, and data analysis was carried out using SEM-PLS with SmartPLS 4.1 software. The research results show that market orientation, product quality and product innovation have a positive and significant influence on the competitive advantage of MSMEs. However, entrepreneurial competence does not have a significant influence on competitive advantage. This research highlights the importance of market orientation, product quality and product innovation in building competitive advantages for MSMEs in the clothing trade sector. Although entrepreneurial competencies do not directly influence competitive advantage, developing these competencies is still important for the long-term success of MSMEs.